Assessing pathological changes within the nucleus ambiguus of horses with recurrent laryngeal neuropathy: An extreme, length‐dependent axonopathy. Issue 6 (9th October 2019) - Draper, Alexandra C.E.; Cahalan, Stephen D.; Goodwin, David; Perkins, Justin; Piercy, Richard J.
Abstract: Introduction: Equine recurrent laryngeal neuropathy (RLN) is a naturally occurring model of length‐dependent axonopathy characterized by asymmetrical degeneration of recurrent laryngeal nerve axons (RLn). Distal RLn degeneration is marked, but it is unclear whether degeneration extends to include cell bodies (consistent with a neuronopathy). Methods: With examiners blinded to RLN severity, brainstem location, and side, we examined correlations between RLN severity (assessed using left distal RLn myelinated axon count) and histopathological features (including chromatolysis and glial responses) in the nucleus ambiguus cell bodies, and myelinated axon count of the right distal RLn of 16 horses. Results: RLN severity was not associated with RLn cell body number ( P > .05), or degeneration. A positive correlation between the left and right distal RLn myelinated axon counts was identified (R 2 = 0.57, P < .05). Discussion: We confirm that RLN, a length‐dependent distal axonopathy, occurs in the absence of detectable neuronopathy.